An ultra-lightweight cellular concrete for geotechnical applications – A review. (June 2022) - Amran, Mugahed; Onaizi, Ali M.; Fediuk, Roman; Danish, Aamar; Vatin, Nikolai Ivanovich; Murali, Gunasekaran; Abdelgader, Hakim S.; Mosaberpanah, Mohammad Ali; Cecchin, Daiane; Azevedo, Afonso
Abstract: For decades, lightweight concrete has been used in various civil engineering applications. Cellular concrete is a type of lighweight concrete that is an emerging composite in materials engineering still. However, due to its low weight, it can be integrated with industrial by-products to develop more advanced composites such as ultra-lightweight cellular concrete (ULCC). ULCC is sustainable and regarded as a potential candidate due to its simplicity of use and other benefits. A systematic review of the potential applications of ULCC in geotechnical construction are presented in this review article. Due to technological breakthroughs and changes in environmental conditions, and their material property is one of the variables that influence the degradation of roadway. Several investigations have been conducted by incorporating different materials into pavement structures to achieve longer-lasting and better pavement infrastructures than those at present. Sustainability benefits, workability, low prices, time, and structural capacity are factors that have been widely focused. This study focuses on the raw materials, production techniques, types, and properties of the ULCCs. The boundary densities of the ULCCs were considered from 400 to 1600 kg/m 3 . Structures all across the globe have benefited from the usage of cellular concrete in some form or another. However, much work in this field should be focused on, particularly in geotechnical applications. Geotechnical applications need specific attention to develop this kind of concrete with enhanced qualities. In order to address this need, this review paper has extensively focused on raw materials, manufacturing procedures, cellular concrete characteristics, types and uses of ULCC, particularly in geotechnical applications. Furthermore, several limitations and gaps in ULCC application in highway construction are highlighted, and recommendations on further improving its use and performance are provided.